2017
DOI: 10.5604/12321966.1232090
|View full text |Cite
|
Sign up to set email alerts
|

Anti-thyroidal peroxidase antibodies are associated with thyrotropin levels in hypothyroid patients and in euthyroid individuals

Abstract: Objective. The study was designed to evaluate the relationship between thyroid antibodies and gland dysfunction, with the aim of finding a clinically useful threshold value of thyreoperoxidase antibodies, which could prove to be predictive for thyroid failure. Materials and method. The study was conducted on 99 women, ages ranging from 18-91 years (mean age: 45.5 ±17.0), were treated as outpatients in the Department of Endocrinology, Metabolism and Internal Medicine. Analysis of serum samples for TSH concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(15 reference statements)
1
1
1
Order By: Relevance
“…This is accompanied by the presence of anti-thyroid antibodies, mainly TPO and anti-thyroglobulin antibodies, which are considered biomarkers of thyroid gland damage (Radetti 2014). In contrast with the 60% established by Bromińska et al (2017) and Malathi et al (2013) and the 50% established by Jayashankar et al (2015), the present study found an SCH level of 15.7% in the presence of TPO-Ab (> 35 UI/ml). Therefore, autoimmune disorders would not be the main cause of SCH in the families of the study population.…”
Section: Discussioncontrasting
confidence: 99%
“…This is accompanied by the presence of anti-thyroid antibodies, mainly TPO and anti-thyroglobulin antibodies, which are considered biomarkers of thyroid gland damage (Radetti 2014). In contrast with the 60% established by Bromińska et al (2017) and Malathi et al (2013) and the 50% established by Jayashankar et al (2015), the present study found an SCH level of 15.7% in the presence of TPO-Ab (> 35 UI/ml). Therefore, autoimmune disorders would not be the main cause of SCH in the families of the study population.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, Fawzi et al [17] found that T3, T4 and TSH are recorded a high significant difference between healthy and hyperthyroidism patients. On the other hand, our results seem to agree with those obtained by Nadhaif et al [18] who found significant differences in TPO antibodies levels between healthy and hyperthyroidism patients. Other studies found a slight increase in TPO antibodies level in hyperthyroidism patients [18].…”
Section: Resultssupporting
confidence: 93%
“…Regarding gender association Anti TPO Ab was found among (71) females while only six male cases found to be Anti TPO Ab positive with significant differences (p value 0.032). and this were in agreement with a study done by Bromińska, et al 19 In our study; we found that Anti-TSH receptor Ab was higher among hyperthyroid cases which was positive in (18 from a total 21 cases 86%) with significant differences (p value 0.019). and this result was agreed by (Mistry et al).…”
Section: Discussionsupporting
confidence: 94%